2014
DOI: 10.3390/jcm3020646
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Sphingolipid Metabolism in Pancreatic β Cell Dysfunction Induced by Lipotoxicity

Abstract: Pancreatic β cells secrete insulin in order to maintain glucose homeostasis. However, various environmental stresses such as obesity have been shown to induce loss of secretory responsiveness in pancreatic β cells and pancreatic β cell apoptosis which can favor the development of type 2 diabetes (T2D). Indeed, elevated levels of free fatty acids (FFAs) have been shown to induce β cell apoptosis. Importantly, the chronic adverse effects of FFAs on β cell function and viability are potentiated in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 95 publications
1
32
0
Order By: Relevance
“…Previous studies have reported that ceramide and oxidative stress are intimately related to cell death induction [34]. Recently, there have been reports that the development of nonalcoholic steatohepatitis or pancreatic β-cell dysfunction in patients with type 2 diabetes mellitus is associated with an increase in ROS by ceramide [35,36]. Moreover, in human myeloid leukemia U937 cells, it has been reported that ceramide elicits a direct effect on mitochondria to overproduce ROS, causing inhibition of the respiratory chain [37] and increasing permeability of the mitochondrial membrane to form ceramide channels that increase cytochrome C release [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ceramide and oxidative stress are intimately related to cell death induction [34]. Recently, there have been reports that the development of nonalcoholic steatohepatitis or pancreatic β-cell dysfunction in patients with type 2 diabetes mellitus is associated with an increase in ROS by ceramide [35,36]. Moreover, in human myeloid leukemia U937 cells, it has been reported that ceramide elicits a direct effect on mitochondria to overproduce ROS, causing inhibition of the respiratory chain [37] and increasing permeability of the mitochondrial membrane to form ceramide channels that increase cytochrome C release [35].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating lipids and lipid metabolism are integrally related to type-2 diabetes (T2D) and sphingolipids specifically act as mediators of fatty acid-induced b-cell dysfunction, with possible therapeutic implications. 43,44 Interestingly, we found euricoyl-sphingomyelin associated with 25(OH)D. Given its role in sphingolipid metabolism, an increase in this metabolite could lead to production of sphingolipids necessary to reduce b-cell dysfunction in T2D. A recent Mendelian randomization study demonstrated an association between genetic variants of low plasma 25(OH)D (specifically DHCR7) and T2D, suggesting a possible causal relationship between serum vitamin D and this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, enrichment of modules for sphingolipid metabolism in the GDM group may hint at a potential role of gut microbiota in inflammatory signaling (Maceyka and Spiegel, 2014), as bacterial sphingolipid production resulted in changes in host sphingolipid metabolites (Brown et al, 2019), and sphingolipid metabolism was a converging point linking excess free fatty acids and inflammation aroused by adipose-derived inflammation (Kang et al, 2013). Moreover, sphingolipid metabolism also played a crucial role in glucolipotoxicity induced apoptosis and loss of function of pancreatic β cells, contributing to the progression of insulin resistance (Kang et al, 2013;Veret et al, 2014). Consistent with the findings in T2DM and obesity (Haus et al, 2009), the link between sphingolipids, inflammation, and insulin resistance was likely responsible for GDM pathology.…”
Section: Alterations In Gut Microbial Composition and Functional Annomentioning
confidence: 99%